Understanding pastoralist adaptations to drought via games and choice experiments: Field testing among Borana communities - Bell, Andrew Reid; Rakotonarivo, O. Sarobidy; Zhang, Wei; De Petris, Caterina; Kipchumba, Adams; Meinzen-Dick, Ruth S. (Resilience Alliance, Inc., 2025)
Transhumant and nomadic pastoralism in arid and semi-arid spaces from West through Central, East, and Southern Africa is regarded as critical to regional system resilience and food security. Although pastoral systems are highly adapted and adaptive to uncertainty and change, recent decades of severe climatic events and increasing resource pressure are pushing pastoral systems to adopt novel norms and practices. Importantly, forage residue conservation and private forage enclosures are becoming important practices among herders and non-herders alike. As one part of considering the relevance of these responses in shaping the future trajectory of transhumant pastoralism, we developed a multi-part intervention for measuring and observing preferences in pastoral systems, including a novel experimental game called GreenReserve, and tested it in Borana communities in northern Kenya. We found that GreenReserve captured dimensions of human-environment dilemmas faced by pastoralists, and shifted preferences around herd size, losses, and the use of time, as measured through a repeated discrete choice experiment. We found game groups with younger players and with more female players to include more exploration of pastoral adaptations such as the use of grass reserves and the harvesting of grass, as well as to have less conflict within the game. We also observed both preferences as well as game strategy to shift along the length of the study: as the region moved further into a drought and failed short rainy season, players were more conscious of large herds, bad rainfall-year losses, and made better use of reserves in game play, though it was beyond the scope of the current study to determine causality. Future research is needed to unpack the mechanisms underlying the variations and possible shift in preferences and subsequently help identify entry points for targeted interventions (including agricultural extension services) to support pastoral communities in climate change adaptation. Further, these first fieldwork findings suggest two key dimensions for expanded work beyond this study to identify whether mixed methods approaches such as this aid experiential learning in agriculture contexts.